2018
DOI: 10.1371/journal.pone.0193487
|View full text |Cite
|
Sign up to set email alerts
|

Gait symmetry and hip strength in women with developmental dysplasia following hip arthroplasty compared to healthy subjects: A cross-sectional study

Abstract: IntroductionUntreated unilateral developmental dysplasia of the hip (DDH) results in asymmetry of gait and hip strength and may lead to early osteoarthritis, which is commonly treated with a total hip arthroplasty (THA). There is limited knowledge about the obtained symmetry of gait and hip strength after the THA. The objectives of this cross-sectional study were to: a) identify asymmetries between the operated and non-operated side in kinematics, kinetics and hip strength, b) analyze if increased walking spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Few systems can cover a wide range of parameters. For the measurement of 3D JK and STP it is common to use a marker based optical motion capture (OMC) system in combination with force or pressure plates [6,7]. However, OMC systems tend to be expensive, laboratory-bound and their usage tends to be time consuming and needs expert knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Few systems can cover a wide range of parameters. For the measurement of 3D JK and STP it is common to use a marker based optical motion capture (OMC) system in combination with force or pressure plates [6,7]. However, OMC systems tend to be expensive, laboratory-bound and their usage tends to be time consuming and needs expert knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…31 It has been demonstrated that gait asymmetry increases with increased speed. 21 In contrast, Leijendekkers et al 20 found that increased walking speed in THA patients did not result in increased asymmetries in gait kinematics and kinetics. Their findings might be explained by the findings from Lee et al 32 who demonstrated that a larger sway is associated with increased gait velocity in those with a clinical normal gait but not in those with abnormal gait pattern, and that the relationship between trunk sway and gait velocity differs depending on whether gait is clinically normal.…”
Section: Discussionmentioning
confidence: 93%
“…However, others have found that THA patients are significantly weaker and have differences regarding gait symmetry compared with healthy subjects. 20,28 Rapp et al 28 found that THA patients had improved gait symmetry after an intensive rehabilitation program, but they were still impaired 1 mo postoperatively compared with healthy control subjects. It is reasonable to anticipate that just 1 mo of rehabilitation, as demonstrated in the study by Rapp et al 28 was too short a time to restore muscle strength and gait symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isometric strength of the hip abductors was associated with post-operative gait speed. Leijendekkers et al [34] found that hip abduction strength on the operated side was on average 23% lower than that on the non-operated side, and Kubota et al [35] demonstrated that hip abductor muscle strength was significantly correlated with the peak hip abduction moment; indeed, a reduced hip abduction moment after hip fracture may result in an abnormal hip motion, which could slow gait speed. Kline et al [24] found that the strength of the hip extensors and hip abductors on the operated side predicted gait speed after hip fracture.…”
Section: Discussionmentioning
confidence: 99%